Rancang Bangun Visualisasi Panduan Fitness Berbasis Mobile (Studi Kasus: Atlas Sports Club Surabaya) - Arifiansyah, Riska Septian; Sutanto, Teguh; Purnama, Rangsang (Jurnal JSIKA, 2012)
Weight-bearing exercise (fitness) has now become one of the urban lifestyle in the world, especially in Indonesia. The slogan